Antimicrobial Susceptibility Patterns of Streptococcus pyogenes and Non-Groupable Streptococcus Species Isolated from Clinical Specimens in a Tertiary Care Hospital, Lahore: A Cross-Sectional Study - Awais Ashraf; Tehmina Tariq; Azka Mubeen; Hafiz Gull Zaman; Farhan Rasheed; Ijaz Ahmad; Sidra Iqbal (Journal of Health, Wellness and Community Research, 2026)
Background: Streptococcus pyogenes and other Streptococcus species are clinically important pathogens associated with respiratory, skin, soft-tissue, invasive, and toxin-mediated infections. Local antimicrobial susceptibility data are essential for guiding empirical therapy and antimicrobial stewardship, particularly in tertiary-care settings where antibiotic exposure is high. Objective: To evaluate the distribution and antimicrobial susceptibility patterns of S. pyogenes and non-groupable Streptococcus species isolated from clinical specimens in a tertiary-care hospital in Lahore, Pakistan. Methods: This laboratory-based cross-sectional study was conducted in the Department of Microbiology, Ameer-Ud-Din Medical College/Post Graduate Medical Institute, Lahore, from February 2025 to February 2026. Clinical specimens were cultured on 5% sheep blood agar, and Streptococcus isolates were identified using routine microbiological methods. Antimicrobial susceptibility testing was performed by the Kirby–Bauer disk diffusion method according to CLSI criteria. Data were analyzed using frequencies, percentages, and organism-specific denominators. Results: Among 19,500 processed specimens, 165 were Streptococcus-positive, giving a positivity rate of 0.85%. Of these, 14 isolates were S. pyogenes and 151 were non-groupable Streptococcus species. Non-groupable isolates showed high susceptibility to ceftriaxone, teicoplanin, vancomycin, linezolid, penicillin, and ampicillin, whereas S. pyogenes showed highest susceptibility to teicoplanin, vancomycin, and linezolid. Reduced susceptibility was observed for erythromycin and clindamycin, particularly among S. pyogenes isolates. Conclusion: Penicillin and selected β-lactam agents retained substantial in-vitro activity against streptococcal isolates, while macrolide and lincosamide susceptibility was reduced. Routine susceptibility testing and local antibiogram surveillance are necessary to support rational antibiotic selection